A comparative study to observe the effects of online lectures and flipped classroom-assisted sessions among first-phase MBBS students during the COVID-19 pandemic - Arunima Chaudhuri (Journal of the Scientific Society, 2024)
Background: The past decade has encouraged learner-centered approaches which expect students to take greater responsibility for their learning and support each other's progress. The flipped classroom (FC) is a teaching–learning tool that uses learner-centeredness. The present comparative study was conducted to observe the effects of online lectures and FC-assisted sessions among first-phase MBBS students during the COVID-19 pandemic. Materials and Methods: The present study was conducted after taking institutional ethical clearance and informed consent of the participants. Two hundred first MBBS students participated and were divided into two Groups A and B. Ten topics of neurophysiology were taught to both groups using either FC-assisted self-directed learning (SDL) sessions or online lecture classes. A cross-over of groups was done to prevent any bias. Pretest and posttest scores of all topics were assessed using multiple-choice questions (MCQs) and feedback was taken. Program evaluation was done. Results: There was no significant difference in performance in pretest MCQ examinations between the two groups. Students of both Groups A and B performed significantly better in posttest MCQ examinations as compared to pretest MCQ examinations. However, the posttest results of the FC group were better. Faculty and students provided positive views in support of the sessions. Students were highly satisfied with the program. Conclusions: FC needs to be introduced in medical schools early, to help young medical students to develop SDL skills which will enhance their ability to become lifelong learners and improve the quality of patient care in long run.